Charophytes: Evolutionary Ancestors of Plants and Emerging Models for Plant Research - Zo (Frontiers Research Topics, 2017)
The charophytes are the group of green algae that are anestral and most closely related to land plants. Today, these organisms are not only important in evoutionary studies but have become outstanding model organisms for plant research.